The death of the maiden in classical Athens - Margariti, Katia, (Access archaeology., 2017)
This study examines the death of maidens in classical Athens, combining the study of Attic funerary iconography with research on classical Attic maiden burials, funerary inscriptions, tragic plays, as well as the relevant Attic myths. The iconography of funerary reliefs focuses on the idealised image of the deceased maiden, as well as the powerful bonds of love and kinship that unite her with the members of her family, whereas the iconography of vases emphasises the premature death of the maiden, the pain of loss and mourning felt by her family, as well as the observance of the indispensable funerary rites concerning her burial and 'tomb cult'.